The Effect of Alkyl Spacers on the Mixed Ionic‐Electronic Conduction Properties of N‐Type Polymers. (20th January 2021) - Maria, Iuliana P.; Paulsen, Bryan D.; Savva, Achilleas; Ohayon, David; Wu, Ruiheng; Hallani, Rawad; Basu, Aniruddha; Du, Weiyuan; Anthopoulos, Thomas D.; Inal, Sahika; Rivnay, Jonathan; McCulloch, Iain; et al.
Abstract: Conjugated polymers with mixed ionic and electronic transport are essential for developing the complexity and function of electrochemical devices. Current n‐type materials have a narrow scope and low performance compared with their p‐type counterparts, requiring new molecular design strategies. This work presents two naphthalene diimide‐bithiophene (NDI‐T2) copolymers functionalized with hybrid alkyl‐glycol side chains, where the naphthalene diimide unit is segregated from the ethylene glycol (EG) units within the side chain by an alkyl spacer. Introduction of hydrophobic propyl and hexyl spacers is investigated as a strategy to minimize detrimental swelling close to the conjugated backbone and balance the mixed conduction properties of n‐type materials in aqueous electrolytes. It is found that both polymers functionalized with alkyl spacers outperform their analogue bearing EG‐only side chains in organic electrochemical transistors (OECTs). The presence of the alkyl spacers also leads to remarkable stability in OECTs, with no decrease in the ON current after 2 h of operation. Through this versatile side chain modification, this work provides a greater understanding of the structure‐property relationships required for n‐type OECT materials operating in aqueous media. Abstract : A fundamental study on side chain engineering of n‐type polymers reveals that substitution of polar side chains with hybrid non‐polar/polar ones improves the performance of electrochemical transistors. This study shows that swelling of the active layer must be controlled to guarantee stable device operation during continuous operation.